Dermatological examination of family members for the diagnosis of NF1. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
In the early years the café au lait spots are often the only sign to suspect the diagnosis of NF1. The graphic shows that at the age of five the café-au-lait spots are present in 100% of cases, whereas plexiform neurofibroma is only present in 22% of cases and Lisch nodules in 17% of cases (2). The genetic investigation, not easy to perform for the lack of hot spots in the very long NF1 gene, is charged by at least 10% of false negativity. In this situation the dermatological examination of the family members, meticulously conducted by an expert can confirm the diagnosis of NF1, as in the two cases presented here. In the first of the two cases to strengthen the suspicion of NF1 there was also the presence of nevus anemicus, which according to some Authors (1) may enter among the diagnostic criteria for NF1.